Caractéristiques socio-démographiques et dynamique de la transhumance des bouviers peuls de la Nouhao au Burkina Faso - Sidonie Ouoba-Ima (VertigO)
The study aims to characterize the Fulani herdsmen of Nouhao and to analyze the dynamics of transhumance in the pastoral zone. Set in the pastoral area since 1985, farmers have settled and keep livestock and agriculture. This installing was preceded by several achievements including the development of the pastoral zone with an area of 95,000 hectares, the delimitation of the pastoral zone by two long firewalls 172 Kilomètres, breeders about installing the farmhouses ten hectares and the production of livestock infrastructure (wells and vaccination parks). Despite the availability of these pastoral infrastructures and arrangements, farmers have kept their traditional operating system of grazing resources and livestock. One of the traditional system elements is the practice of internal and external mobility to the pastoral zone. The drovers or "duroobè" Fulfuldé are responsible to exercise this pastoral task. The analysis revealed that the drover was Passed on from father to son : 88.90 % of the surveyed household heads use their own children. Most farmers (61 %) have 2 drovers for internal and external transhumance in the pastoral zone, followed by 28.70 % of farmers who have 3 drovers. This was handled increasingly by older people (at least 50 years) and mature enough young age (at least 20 years) against fifteen (15) in the past years. The pastoral area is exposed to bush fires, an abusive cutting fresh wood and early depletion of Nouhao river.